Experimental study on the hysteresis behavior of L-shaped double-skin composite wall with concrete-filled steel tubes. (15th October 2021) - Chen, Zongping; Liang, Yuhan; Liu, Xiang; Cai, Jingming
Highlights: The seismic behavior of L-shaped DSCW was analyzed. The influences of different parameters were discussed. The failure mechanisms were investigated based on strain analysis. The composite effects of different components were discussed. Abstract: In this paper, the seismic behavior of L-shaped double-skin composite wall (DSCW) with concrete-filled steel tubes were investigated. The influence of different parameters, i.e., axial compression ratio, shear span-to-depth ratio, corrugation size, corrugated arrangement, flange size and CFST side column were discussed based on cyclic tests. The hysteresis behavior of DSCW specimens in terms of hysteresis curves, skeleton curves and rigidity deterioration were analyzed. The failure mechanism, as well as the composite effect between each component was also compared based on the strain analysis. It was concluded that the L-shaped DSCW has favorable seismic ductility and toughness with the maximum lateral drift angle of 3%. With the increase of axial compression ratio, the peak load of DSCW specimens increased while the post-peak ductility decreased. By contrast, the peak load of DSCW specimens decreased with the increase of shear span-to-depth ratio. More corrugations are effective to increase the seismic behavior of L-shaped DSCW and it was recommended that the corrugations should be arranged vertically. The flange size has limited influence on the failure processes and carrying capacity of DSCW specimens, while the stress distribution was highly dependent on the flange design of DSCW. The application of concrete-filled steel tubes (CFST) side column is effective to increase the seismic behavior of DSCW and also has significant influence on the composite effect between each component.